HUBUNGAN MOTIVASI BELAJAR DENGAN MINAT WIRAUSAHA PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN - RIZA, YULIA; Hayatunnufus, Hayatunnufus; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2014)
This research was motivated by the existence of problems in the field that showed low student interest in entrepreneurship . The purpose of this study is to look at the relationship between learning motivation and student interest in entrepreneurship education Prodi Makeup and Beauty KK FT UNP . The population in this study were students Year in 2008, 2009 and 2010 Education Program and Beauty Makeup FT UNP Family Welfare Department , amounting to 66 people and the entire population sampled . As a Likert scale instrument that has been tested for validity and reliability . Percentage Analysis using correlation analysis using the Pearson Product Moment Correlation and continued with the t test for the significance of the correlation analysis and to test the hypothesis . The results showed that , on learning motivation variable Achievement Level Respondents obtained a score of 58% in the low category , then the variable interest in entrepreneurship shows the percentage score of 60 % is also the low category . The results of correlation analysis to calculate the degree of relationship of the two variables showed a correlation coefficient of 0.527 rate with the interpretation that is strong enough relationship between the two variables , while for the significance and correlation koorfisien for hypothesis testing using t-test scores obtained 7.262 > 2.000 . Ha which reads thus there is a positive and significant relationship between learning motivation and interest in entrepreneurship with a confidence level of 95 %. Keywords : Motivation , Entrepreneurial Interests